"Suddenly a Binge Drinking Episode Has Happened to Him": Locus of Control, Notion of Responsibility, Alcoholism and Suicide in the Taz Region, Yamal Nenets Autonomous Okrug - Kirill V. Istomin (Journal of Ethnology and Folkloristics)
Although the notion of responsibility is often invoked by mass-media reports, activists and lay people when discussing alcoholism and suicides, anthropological discussions of this topic seem to deliberately avoid the notion. Based on the example of the Taz Nenets of western Sibera, this paper explores how cross-cultural differences in the notion of responsibility, if approached in a non-moralising way, can enrich our understanding of several aspects of the drinking and suicidal behaviours of native northerners. The Nenets seem to believe that both positive and negative events in their lives happen more due to chance or for highly localised reasons that they do not control rather than being caused by their own informed and wilful actions (external locus of control). Particularly, acts of suicide and binge drinking episodes just happen to people and, therefore, people cannot be held responsible for them. This attitude can be a compensatory mechanism for the flat attribution style observed among Nenets in previous studies. It should be taken into account in programs of suicide prevention and the treatment of alcoholism.